PELAKSANAAN PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KELURAHAN RINTIS KECAMATAN LIMAPULUH KOTA PEKANBARU TAHUN 2017 - Siti Rafiqah Salima; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Slum settlement problems are still a major problem faced in urban settlements in Indonesia to date, the rate of population growth through the process of urbanization and the rate of population growth that arises due to high annual birth rates while the availability of supporting facilities and infrastructure for residential areas has not been well fulfilled and under minimum service standards (SPM) such as the lack of provision of public service facilities and infrastructure, low quality of drinking water, drainage, waste, solid waste services and building density issues that can have an impact on fulfilling fire protection. One of the kelurahan in Pekanbaru City which is included in the slum area is the Rintis Village. Rintis Village is incorporated into the Coastal Village and Tanjung Rhu Village into one area called the Coastal Slum Zone, the slum area of the area is 23.00 Ha, and each kelurahan has different slum areas, Kelurahan Pesisir 6.40 Ha, Kelurahan Pioneering 9.50 Ha, and Tanjung Rhu Village 7.10 Ha. This study aims to determine the implementation of the No Slum City Program (KOTAKU) in the Rintis Village of Limapuluh Kota Pekanbaru District in 2017 and analyze the factors that influence the implementation of the KOTAKU Program, namely, the characteristics of the problem, policy characteristics and policy environment. The research locations are the Department of Public Housing and the Pekanbaru City Settlement Area, the Coordinator of the Pekanbaru KOTAKU Program, and the Rintis Village which are the main sources of this research. The results of this study are that the implementation of the KOTAKU Program in the Rintis Sub-District of Limapuluh Kota Pekanbaru District in 2017 has not been optimal. This is because the implementation of the KOTAKU program in Rintis Village in 2017 does not meet the characteristics that affect the success of implementing a program. Keywords : KOTAKU, Characteristic Problem, Policy Characteristic, Policy Environment